WHO IS TO BLAME FOR MOST EMPLOYEES QUITTING THEIR JOBS? A COMPREHENSIVE ANALYSIS ON THE JUSTIFICATION OF BOTH SIDES: MANAGER/BOSS OR EMPLOYEES - Santi Prianti Edo (Sekolah Tinggi Ilmu Ekonomi GICI, 2025)
The research examines how Kupang City of East Nusa Tenggara Province Indonesia managers and ex-staff members determine employee exit causes while studying their contrasting workplace attitudes. The research employed a comparative survey design with purposive sampling to obtain data from 50 managers and 50 former employees working in various industries. The quantitative analysis through mean score evaluation and perception gap assessment showed managers blame employee behaviour for turnover because of disloyalty and poor motivation and unrealistic expectations but former employees point to management failures in leadership and career growth and employee recognition. The study found that former employees and current managers disagree most strongly about career development opportunities and work-life balance support. The research adds to human resource management theory and practice through its analysis of how attribution biases and cultural-contextual factors affect employee turnover perceptions in a developing regional economy. Organizations can develop better retention strategies and build trust-based relationships through understanding these perception differences